Bisphosphonates and Cancer: A Relationship Beyond the Antiresorptive Effects - Teixeira, Sonia (2019)
Bisphosphonates (BPs) are stable analogues of the Inorganic Pyrophosphate (PPi), an endogenous regulator of bone mineralization, which can resist the hydrolysis in the gastrointestinal tract. Their conformation allows targeting the bone as a result of their three-dimensional structure, which makes them primary agents against osteoclast-mediated bone loss. They are used in many bone pathological conditions, like bone metastasis, because of its ability to modulate bone metabolism into a less favorable place to cancer cell growth, through the inhibition of osteoclastogenesis and bone resorption. This review is focused on the mechanisms of action through which BPs affect the cellular activity and survival, mainly on their antitumoral effects. In conclusion, BPs are considered the primary therapy for skeletal disorders due to its high affinity for bone, but now they are also considered as potential antitumor agents due to its ability to induce tumor cell apoptosis, inhibition of cell adhesion, invasion and proliferation, modulation of the immune system to target and eliminate cancer cells as well as affect the angiogenic mechanisms. Like any other drug, they also have some adverse effects, but the most common, the acute phase reaction, can be minimized with the intake of calcium and vitamin D.